Analysis of the potential billboard tax on Local Original Revenue (PAD) of Serang Regency - Putri, Siti Hilma; Handayani, Putri; Yuliani , Aisyah Sylvia; Haryanti , Putri; Wahyudi, Wahyudi (Jurnal Mantik, 2024)
This study aims to determine the effectiveness of billboard tax revenue on local original revenue in Serang Regency in 2017-2021 and to find out how much the billboard tax contributes to Serang Regency original revenue. This research uses qualitative descriptive methods. The type and source of data used is secondary data. Data analysis techniques are summarizing data, presenting data, and analyzing data. The result of this study is the revenue or realization of the billboard tax in Serang Regency with a target each year. Serang Regency Always experiences good achievements, namely the realization that the billboard tax always exceeds the targeted value every year and that the billboard tax has the potential to increase the Local Original Revenue of Serang Regency, which will be obtained in 2024, is Rp. 3,655.752.517